Connecting the bee dots - Mardan, Makhdzir (Universiti Putra Malaysia Press, 2008)
In his autobiographical account that traces and chronicles three defining dots of bee-related events, Makhdzir recognizes and acknowledges what spawned and shaped his interest and enthusiasm on bees over the last 50 years. His passion with bees evolved from his childhood days and over time those telling dots of bee encounters eventually turned out to be the catalyst for his career and profession. The three defining encounters with bees were: i) the behaviour of temperature regulation of a Giant honeybee (Apis dorsata) colony, at age five; ii) the gallery-nesting behaviour of carpenter bees (Platynopoda latipes) on wooden beams of a house, at age ten; and, iii) the harvesting of honey from Giant honeybee colonies, at age five. His observations of the contracting and expanding size of Giant honeybee colonies on hot and rainy days haunted him again in later years and he followed up on his curiosity by making it the subject for his Ph. D. thesis research. Through experimental manipulation, temperature monitoring of the body parts (head, thorax and abdomen) of the bees that enveloped the open-nesting, broodright colonies of A. dorsata to form a protective curtain showed that there were significant body temperature differences (less than 2 0C ) between curtain bees with fluid content in their honeycrops and those without. The fluid (water) in their honeycrops, afforded the curtain bees the opportunity for evaporative cooling by extruding and re-imbibing the fluid content on their mouthparts, in what was termed as gobbetting. The gobetting behaviour was experimentally shown to be stimulated by directing air currents onto the curtain bees that sought incidental evaporative cooling from any passing breeze. Under excess heat stress, during high ambient humidity and temperature, the colony resorted to performing colony en masse airborne defecations (CEMA) by the curtain bees to dissipate heat load. Usually more than 50% of the bees in the colony take flight to defecate en masse whereby the subsequent advantage is reduced body weight through loss of bee feces, and hence reduced heat load for cooling. The monitoring of CEMAs from morning till dusk serendipitously led to the discovery of the clockwork regularity of drone mating flights that occurs everyday at sunset where the incidence of loss of brightness was experimentally shown to modulate the onset of drones flying out to drone congregation areas in the direction of sunset in the horizon The second bee dot event of childhood days was playing kites with captured, gallery-nesting, carpenter bees, which also connected 25 years later to trigger the idea to develop a carpenter bee hive design that leverages on the concept of bee space (gap size of the nesting gallery). Efforts to address the nagging questions about a carpenter bee infested log close to the laboratory led to curiosity about the nature of nesting galleries of carpenter bees inside which subsequently led to the development of a multiple-frame, carpenter bee hive. Founding gynes (reproductive females) were enticed to settle in a new adjacent gallery, and prevented from returning to their old nesting gallery by deception, using wooden, dummy entrances. An observation carpenter bee frame hive was developed using plexiglass and restricting gallery construction within the frame width of slightly bigger than the thorax of the carpenter bee (bee space of 2.2 cm). Hive boxes of carpenter bee nests were introduced and propogated to provide pollination services in passion fruit orchards. The third bee dot event of observing honey hunters harvesting honey from A. dorsata colonies for the first time, led to further forays into the rainforests to observe and learn about the traditional art of honey-gathering from the hundreds of A. dorsata colonies that nest on emergent bee trees in the rainforests of Malaysia and the Asean countries. From research expeditions throughout the Asean region, it was realised that there were observable intricate faunistic associations between the Giant honeybees and its natural enemies of several species of birds, bear, bats, etc. Bee eaters and honey buzzards display adaptive morphological features in overcoming its prey (A. dorsata) displaying a special ability to remove bee stings and adaptive behaviour of subterfuge by using decoy strategy to confuse the colony. In response, the A. dorsata adopts a variety of evasive behaviour for colony defense, such as, colony enlargement by the curtain bees. Both the behavioral responses of the A. dorsata against attacks by its natural enemies and the subterfuge by by several species of birds, ranging from bee eaters ( spp.), honey buzzards (Pernis Apovirus) and falcons (Micrographis fangillarius) and bats that depend on the Giant honeybees for food around the bee trees, display an interplay of defensive behaviour. All three incidents of encounters with Giant honeybees, carpenter bees and honey hunters provided him inspiration for the development model for beekeeping in Malaysia taking into account the resource-needs, or specificity between plants and the type of bees. Different species of plant flowers may have obligate relationship with specific bees. Most important of all, pursuit of an interest with enthusiasm is the key driving force to foster and sustain interest in any endeavour.